Pediatric cancer risk in association with birth defects: A systematic review. - Kimberly J Johnson; Jong Min Lee; Kazi Ahsan; Hannah Padda; Qianxi Feng; Sonia Partap; Susan A Fowler; Todd E Druley (PLoS ONE, 2017)
Background Many epidemiological studies have examined associations between birth defects (BDs) and pediatric malignancy over the past several decades. Our objective was to conduct a systematic literature review of studies reporting on this association. Methods We used librarian-designed searches of the PubMed Medline and Embase databases to identify primary research articles on pediatric neoplasms and BDs. English language articles from PubMed and Embase up to 10/12/2015, and in PubMed up to 5/12/2017 following an updated search, were eligible for inclusion if they reported primary epidemiological research results on associations between BDs and pediatric malignancies. Two reviewers coded each article based on the title and abstract to identify eligible articles that were abstracted using a structured form. Additional articles were identified through reference lists and other sources. Results were synthesized for pediatric cancers overall and for nine major pediatric cancer subtypes. Results A total of 14,778 article citations were identified, of which 80 met inclusion criteria. Pediatric cancer risk was increased in most studies in association with BDs overall with some notable specific findings, including increased risks for CNS tumors in association with CNS abnormalities and positive associations between rib anomalies and several pediatric cancer types. Conclusions Some children born with BDs may be at increased risk for specific pediatric malignancy types. This work provides a foundation for future investigations that are needed to clarify specific BD types predisposing toward malignancy and possible underlying causes of both BDs and malignancy.